JAMINAN SOSIAL TERHADAP GELANDANGAN DAN PENGEMIS - Wahyu Ramadhani (Jurnal Hukum Samudra Keadilan, 2021)
Qanun Number 11 of 2013 concerning social welfare, this is to carry out social development programs at various levels of society. The qanun was issued as a more operational policy which became the legal basis for efforts to carry out protection, social rehabilitation and empowerment.The Social Service has provided guidance and training to homeless people and beggars who have been caught in raids at the Social Protection House (RPS), the guidance and training are given with the aim that homeless people and beggars can open businesses, have decent jobs, and become independent so that they stop to be vagrants and beggars. The social security programs provided to them in the RPS include, such as: health insurance, education, housing and skills. The programs carried out by the Social Service in dealing with homeless people and beggars have so far had the effect of reducing the number of homeless and beggars, this shows the success of the Social Service in reducing homeless and beggars as well as beggars and vagabonds to get their rights as citizens guaranteed in the Laws. Invitation.